2021
DOI: 10.3389/fpsyt.2021.631032
|View full text |Cite
|
Sign up to set email alerts
|

Workers' Decisions to Disclose a Mental Health Issue to Managers and the Consequences

Abstract: Background: Stigma can be a barrier to accessing effective interventions and work accommodations for mental illnesses. Fear of stigma's concomitant prejudice and discrimination can inhibit workers from asking for help. Thus, it may be important to develop effective interventions addressing workplace stigma. To identify important targets for these interventions, this study addresses three questions: (1) what proportion of workers experiencing mental health issues disclosed their mental health issue to their man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 32 publications
5
33
2
Order By: Relevance
“…Nevertheless, overall respondents tended to be optimistic about the outcomes of disclosure, for instance illustrated by the finding that in 11 out of 14 different circumstances, they would advise a good friend to disclose. The tendency for optimism found in this study was also found in two Dutch studies, where about 75% of workers with [19] and without [20] mental illness indicated they actually had or would disclose, respectively. The contradictory finding that respondents were generally positive in their expected disclosure outcome yet believed it could lead to discrimination in the form of job loss or career advancement is puzzling and needs to be studied in future research.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, overall respondents tended to be optimistic about the outcomes of disclosure, for instance illustrated by the finding that in 11 out of 14 different circumstances, they would advise a good friend to disclose. The tendency for optimism found in this study was also found in two Dutch studies, where about 75% of workers with [19] and without [20] mental illness indicated they actually had or would disclose, respectively. The contradictory finding that respondents were generally positive in their expected disclosure outcome yet believed it could lead to discrimination in the form of job loss or career advancement is puzzling and needs to be studied in future research.…”
Section: Discussionsupporting
confidence: 85%
“…For example, a study among Dutch employees showed that compared with people who had disclosed their MHC/SA, those who had not were significantly younger. 22 However, generalisability was not the purpose of the study. As with other qualitative studies, the aim was to provide insight into a complex challenge of which more knowledge is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Another study among Dutch workers found that of those who had disclosed MHC/SA, almost 50% indicated this was due to a good relationship with their manager, and the main reasons for reporting a positive or negative disclosure experience was due to whether support was received or not by the manager. 22 This indicates the importance of supervisor–worker relationships for disclosure. As research on the topic is scarce, and the decision to disclosure has major consequences for health, well-being and sustainable employment, it is important to further examine factors that influence disclosure.…”
Section: Introductionmentioning
confidence: 99%
“… 67 Next was safety (n=12) in terms of being outside of workplace setting (n=6), confidential (n=5) and positive (n=1), which could help to overcome some workplace barriers such as fear of discrimination or repercussion on career. 12 15 Relatability (n=12) was reported next. This referred to COs being a non-clinical and less stigmatising setting (n=8) and including people to which participants could relate (n=4).…”
Section: Discussionmentioning
confidence: 96%
“… 10 11 Workplace barriers include mistrust of embedded programmes such as employee assistant programmes, fear of discrimination or repercussion on their career, limited confidence in managers’ capabilities surrounding disclosure and unsupportive organisational cultural norms. 12–15 Furthermore, structural barriers such as the unavailability of service providers outside working hours can also affect access to care. 11 …”
Section: Introductionmentioning
confidence: 99%